Mindful eating practice predicts lower body mass index among university students - Ahmad, Salwani; Sidek, Suriati; Hamirudin, Aliza Haslinda; Mohd Abu Bakar, Wan Azdie; Unal, Tubanur Irfan (Asian Network for Scientific Information, 2019)
Background and Objective: The hectic life of university students may contribute to mindless eating and eventually may lead to obesity. Previous studies suggested that adopting mindful eating practice has a positive influence on eating habit modification and obesity rate reduction. Hence, this study aimed to assess the role of mindful eating practice and health attitudes in predicting the body mass index (BMI) of university students. Materials and Methods: A cross-sectional study was conducted among 300 university students at the International Islamic University Malaysia (IIUM). Participants’ weight and height were measured and they were required to complete the Mindful Eating Questionnaire (MEQ) and Health Attitude Scale (HAS). Results: The mean body mass index (BMI) of participants was 22.53±4.00 kg mG2 . The highest mean reported for the mindful eating practice subscale is the awareness subscale (mean = 2.7852±0.475). The results showed that a higher MEQ score predicted a lower BMI (p<0.05) and this explained 2% of the variance in BMI. However, BMI was not predicted by health attitudes. Conclusion: The results suggested that the concept of mindfulness has a positive impact on body weight, which could be incorporated into weight loss and weight maintenance intervention programmes.